Barriers to Practical Learning in the Field: A Qualitative Study of Iranian Nursing Students' Experiences - Jahanpour; Azodi; Azodi; Khansir (Kashan University of Medical Sciences, 2016)
Background Clinical training is an integral part of nursing education; however, some studies have shown that it is not always efficient. Objectives This study aimed to find out the factors that can impede nursing students' clinical learning. Materials and Methods In this qualitative study, data were collected via reflective journal writing. Purposeful sampling was used, and 12 senior nursing students were recruited to the study. The data were analyzed using a content analysis method. Results Three main categories were derived, including inappropriate communication, ineffective role models, and theory-practice gaps. Students perceived that inappropriate communication between instructors, staff members, and students had the greatest impact on student learning. The competence of clinical instructors and staff is an important factor affecting students' training. The clinical learning environment does not always integrate theory and practice together. Conclusions Nursing students did not experience effective clinical learning. Having expert instructors and supportive communication are important factors in creating a clinical learning environment.